Use of an Immersed Mesh for High Resolution Modeling of Film Cooling Flows - Lad, B; He, L (2013)
The development of a high pressure turbine requires the accurate prediction of flow within and around film cooling holes. However, the length scales inherent to film cooling flows produce a large disparity against those of the mainstream flow; hence they cannot be resolved by a mesh generated for an aerodynamics analysis. Furthermore, the process of meshing cooling holes is not only time consuming but cumbersome; thus making the parametric study of film cooling effectiveness for a given blade geometry, using hole geometry and distribution, very difficult in a design environment. In this paper an immersed mesh block (IMB) approach is proposed which allows the refined mesh of a cooling hole to be immersed into the coarser mesh of a nozzle guide vane (NGV) and solved simultaneously while maintaining mass conservation. By employing two-way coupling, the flow physics in and around cooling holes is able to interact with the mainstream; hence the length scales of both types of flow are appropriately resolved. A generic cooling hole design can then be mapped to a given aerofoil geometry multiple times to achieve an appropriate distribution of cooling holes. The results show that for a realistic transonic blade, a configuration consisting of up to 200 cooling holes can be efficiently and accurately calculated-while retaining the original aerodynamic mesh but with a much enhanced resolution for the film cooling. © 2013 American Society of Mechanical Engineers.